Methodological Quality Assessment of Budget Impact Analyses for Orphan Drugs: A Systematic Review - Abdallah, Khadidja; Huys, Isabelle; Claes, Kathleen; Simoens, Steven (Frontiers in Pharmacology, 2021)
Objectives: This research aims to evaluate the methodological quality of budget impact analyses for orphan drugs and to provide suggestions for future analyses. Methods: Conference abstracts and peer-reviewed literature on budget impact analyses were collected through searches of Pubmed and Embase. ISPOR good practice guidelines were used as a methodological standard for budget impact analyses. Examined parameters encompassed: perspective, target population, data sources, intervention and comparator(s), time horizon, scope of costs, discounting, validation, assumptions and sensitivity analysis. Results: Seventy studies on individual orphan drugs and 21 studies on a combination of orphan drugs analysing budget impact were identified. Overall, analyses considered a third-party payer perspective, reported periodic budget impacts over a one-to-five-year time horizon, and did not apply discounting. A dynamically fluctuating population and costs beyond drug costs were accounted for in 18.7% and 51.7% of studies, respectively. Input data were retrieved from published literature, clinical trials, registries, claims databases, expert opinions, historical data and market research. Assumptions were mostly made about population size and intervention/comparator(s) market uptake, but these assumptions were rarely justified and their impact was insufficiently explored through sensitivity analyses. Budget impact results were rarely validated. Conclusions: Existing budget impact analyses for orphan drugs are concise, vary greatly and are of substandard methodological quality. To eliminate possible bias in future budget impact analyses, future studies should adhere to national or ISPOR good practice guidelines on budget impact analysis.